EMBRACING RESTORATIVE JUSTICE: A PATH TOWARDS EQUITABLE MEDIATION IN CRIMINAL CASES - Agusta, Evelin Nur (Doctoral of Law Program, Faculty of Law, Universitas Diponegoro, 2024)
Mediation is a viable option in criminal cases, as it adheres to the principle of achieving a fair and equitable form of justice. Restorative justice is a process that aims to resolve criminal cases by incorporating the perpetrator, victim, perpetrator’s family, and other relevant parties. The goal is to collectively seek a fair conclusion that focuses on restoring the original condition rather than seeking revenge. This essay elucidates the imperative nature of utilising media in criminal cases to achieve restorative justice. Restorative justice has been adopted somewhat in general criminal cases by law enforcement. Execution of Restorative Justice. Furthermore, it aligns with the core principles of our nation, Pancasila, which emphasises the importance of equilibrium, unity, peaceful coexistence, equality, fraternity, and collective decision-making. If Restorative Justice is implemented appropriately, it aims to give the community a perception of justice and advantageous outcomes.